1/3 plateau and 3/5 discontinuity in the magnetization and the magnetic phase diagram of hexagonal GdInO3 - Yuan, Ning; Elghandour, Ahmed; Hergett, Waldemar; Ohlendorf, Rahel; Gries, Lukas; Klingeler, Rüdiger (Physical review, 2023)
We report the high-pressure optical floating-zone growth of GdInO3 single crystals and show its magnetic phase diagram down to the millikelvin regime as determined by magnetization measurements. The centered-honeycomb lattice structure shows considerable magnetic frustration (|Θ|/𝑇N≃5) and develops long-range magnetic order below 𝑇N=2.1 K from a short-range-ordered paramagnetic phase. Concomitantly, a small net magnetic moment evolves at 𝑇N which points along the crystallographic 𝑐 direction. Upon cooling, the net moment reorients at 𝑇**≃1.7 K and 𝑇*≃1 K. A broad 1/3 plateau indicative of the up-up-down (𝑢⁢𝑢⁢𝑑) spin configuration appears for magnetic fields 𝐵∥𝑐 but is absent for 𝐵∥𝑎⁢𝑏, thereby suggesting easy-axis anisotropy. At 𝑇=0.4 K, a jump in magnetization at ≃3/5 of the saturation magnetization signals a discontinuous transition to a high field phase and we find evidence for a possible tricritical point. Small energy and field scales in the accessible regimes render GdInO3 a well-suited example to study the phase diagram of a semiclassical frustrated hexagonal lattice in the presence of weak easy-axis anisotropy of mainly dipolar origin.
Im Titel ist die Zahl 3 im Ausdruck "GdInO3" tiefgestellt
Gesehen am 27.05.2024